PENGEMBANGAN SISTEM INFORMASI JASA LAUNDRY BERBASIS WEBSITE STUDI KASUS PADA TURTLE LAUNDRY - Rianto Rianto; Giri Purnama (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2023)
Lifestyle changes in today's big cities require someone to be able to manage their time better. This is due to work demands as well as personal matters so they don't have too much time to take care of housework, one of which is washing and ironing clothes. This makes the laundry service business more and more because laundry business people see a quite profitable business potential. Turtle Laundry is a laundry service business located in the Cakung area, East Jakarta. Currently, the management and recording of sales reports still use manual methods which have the potential to paralyze and eliminate data. To find out the results of the current laundry income, you must match all the laundry notes with the records made in the book, so it takes quite a long time and there is a high probability that there will be discrepancies between all the notes and the results. from recording in the book. From these problems the author is motivated to be able to overcome existing problems by creating a website-based Turtle Laundry information system application that can be used to manage transactions and also record sales to make it easier for Turtle Laundry business owners to run their business.